Inducing pinning states and localized patterns in a monolayer of laterally attracting adatoms - Mangioni, Sergio Enrique (2017)
The so-called "entropic mechanism" for ordering noise-induced phase transitions has been formerly used to stabilize nanopatterns in a realistic model for a monolayer of laterally interacting adsorbates. Here, we use this mechanism to stabilize pinning states and induce stochastic localized patterns ("dissipative solitons") on the monolayer. The key to achieve that goal is to displace only one of the stable homogeneous states toward field values at which the lateral interactions can elicit stable nanopatterns. At larger noise intensities, the "soliton" locations fluctuate with larger amplitude. However, since more localized patterns are elicited by the noise, their motion becomes confined when looked at longer timescales.